Quaternization of Vinyl/Alkynyl Pyridine enables ultrafast cysteine‐selective protein modification and charge modulation - Matos, Maria J. (2022)
© 2019 The Authors. Published by Wiley-VCH Verlag GmbH & Co. KGaA. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.